Molecular confirmation, constituents and cytotoxicity evaluation of two medicinal Piper species used by the Manobo tribe of Agusan del Sur, Philippines. (April 2020) - Dapar, Mark Lloyd G.; Demayo, Cesar G.; Meve, Ulrich; Liede-Schumann, Sigrid; Alejandro, Grecebio Jonathan D.
Graphical abstract: Highlights: Molecular confirmation of an indigenous Piper decumanum and an introduced Piper aduncum . Reinforcing ethnoclassification of Piper species using integrative molecular approach. Application of constituent and cytotoxicity evaluation for species comparative analysis. Abstract: The Manobo tribe in the Philippines is culturally rich in ethnomedicinal practices and known to use popular plants locally named as "Lunas" (meaning "cure"). One of these is "Lunas-bagon tapol" which was previously identified as Lunasia sp. (Rutaceae) based on vegetative morphology. The other species is "Lunas-buyo" which is similar in ethnomedicinal use and morphology. This broadly-based study verifies these two "Lunas"-named specimens and evaluates the phytochemicals present and cytotoxic properties. The sequences of nuclear ITS, and plastid rbc L, and mat K were investigated for species identification. Molecular confirmation using BLAST n nucleotide database query revealed that the two confused "Lunas"-named specimens were members of Piperaceae and not Rutaceae. Phylogeny of Asian Piper using ITS sequences revealed "Lunas-bagon tapol" as Piper decumanum L. and "Lunas-buyo" as Piper aduncum L. with strong support (BS = 100 %). Both Piper species similarly showed the presence of alkaloids, flavonoids, steroids, tannins and fatty acids but the absence of cyanogenic glycosides. Also, P. decumanum has moderate amount of saponins while P. aduncum contains moderate amount of anthraquinones. A cytotoxic activity test using trypan blue exclusion method against normal lymphocytes from human blood showed low toxicity (91.9 % viable cells) for P. decumanum and mild toxicity (88.3 % viable cells) for P. aduncum when subjected to 1000 μg/ml of the stem ethanolic extracts. These results support the practical approach of molecular-based taxon identification and provide the biochemical and biological basis as to the constituents present and cytotoxic properties of these medicinal Piper species for future pharmacological research, conservation priorities and ecological management.